2008
DOI: 10.1038/cgt.2008.39
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced human endonuclease G expression suppresses tumor growth in a xenograft model

Abstract: We have developed a hypoxia-inducible gene therapy approach for the expression of the mature form of human endonuclease G to facilitate cell death in hypoxic regions of the tumor. The chimeric therapeutic gene is placed under the control of a hypoxia response element based promoter and contains a translocation motif linked in frame to an oxygen-dependent degradation domain and the endonuclease G gene. Transient expression of the chimeric therapeutic gene in breast and prostate cancer cell lines resulted in eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…EndoG is not only a DNA-cleaving nuclease and a cell death effector but is also a multifunctional protein modulated by intracellular ROS dynamics During the two decades since EndoG was shown to be a cell death effector in C. elegans and mice, most studies have focused on inducing EndoG activity to kill cancer cells [20,21,27] or blocking its activity to induce cytoprotection [28,29]. In this classical view, EndoG is primarily localized in mitochondria during translation and translocates to the nucleus upon apoptotic insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EndoG is not only a DNA-cleaving nuclease and a cell death effector but is also a multifunctional protein modulated by intracellular ROS dynamics During the two decades since EndoG was shown to be a cell death effector in C. elegans and mice, most studies have focused on inducing EndoG activity to kill cancer cells [20,21,27] or blocking its activity to induce cytoprotection [28,29]. In this classical view, EndoG is primarily localized in mitochondria during translation and translocates to the nucleus upon apoptotic insult.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated EndoG levels can sensitize cancer cells to chemotherapeutic drugs [ 18 , 19 ]. Regarding cancer cell death, studies have collectively suggested that increasing ROS levels might be a possible strategy to destroy cancer cells via nuclear EndoG activity because oxidative stress would induce EndoG expression and translocation to the nucleus [ 20 , 21 ]. However, in OC therapy, various types of antioxidants have been used to decrease intracellular ROS alone or in combination with other antitumor reagents [ 9 , 10 ].…”
mentioning
confidence: 99%
“…The development of a theranostic agent for HIF‐1 requires the expression of an imaging reporter in the tumor under hypoxic conditions, and the delivery of a therapeutic payload only where hypoxia is present. HRE has been exploited in several studies to target hypoxia using either prodrug enzymes or suicide genes 18, 19, although, to date, this has not been combined with imaging. As mentioned earlier, the minimization of damage to normal tissues is one of the most sought‐after goals in cancer treatment.…”
Section: Theranostic Imaging Of the Physiological Tmementioning
confidence: 99%
“…CREB is a 43–46 kDa nuclear transcription factor, which has been recognized by our group to be involved in the response to ionising radiation/etoposide combined treatment [Cataldi et al., 2006], and in the events linked to differentiation [Di Pietro et al., 2007] in the same experimental cell model. CREB recognizes the highly conserved sequence known as c‐AMP responsive element (CRE), 5′‐TGACGTCA‐3′, which can be phosphorylated on serine‐133 (Ser‐133) such as PKC, Erk/MAPK and ATM (Ataxia Telangiectasia mutated Protein Kinase) [Yamamoto et al., 1988; Pearson et al., 2001; Stork and Schmitt, 2002; Blois et al., 2004].…”
Section: Introductionmentioning
confidence: 99%